Intelligent caching in high-load systems as a response to the limitations of classical cache management methods - Volokh , Bohdan (Ways to Improve Construction Efficiency, 2023)
The relevance of the work is substantiated by the importance of optimal data processing in highly loaded systems, which is achieved by using caching technology. The problems of effective management of data flows in modern information systems are researched. The basic functions and main types of caching in high-load information systems are considered. The role of caching in ensuring the scalability and stability of highly loaded systems in the conditions of growing requirements for their reliability, adaptability, stability and performance is defined. It is specified that in the realities of modern dynamic, highly loaded distributed systems, there are more and more situations in which these methods become insufficient or ineffective. At the same time, increasing the efficiency of data access, load balancing, reducing latency and ensuring system stability directly depends on a properly organised caching mechanism. The typical limitations of classical cache management methods are analysed. It is shown that methods such as Least Recently Used, Least Frequently Used, First In First Out and their modifications are more often demonstrating limitations in a dynamic environment where changes in the structure of requests, the context of objects and variability of user behaviour play an important role. As a response to the limitations of classical cache management methods for tasks where it is essential to take into account the specifics of queries and user behaviour of different groups, the context and relationships between objects, as well as the dynamics of queries based on their history, the expediency of using intelligent cache management strategies is substantiated. The prospect of development and integration of intelligent cache management components into the operation of high-load systems is shown, which will allow them to learn from real data, predict future requests and make effective decisions on saving or deleting objects from the cache. It has been decided to focus further research on the development of an intelligent caching method that can provide efficient access to relevant data in the information infrastructure of systems in the field of architecture and construction.